2016
DOI: 10.1159/000456032
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Pulmonary Function in Patients with Psoriasis

Abstract: Background: Psoriasis is associated with chronic obstructive pulmonary disease. There is no study on the spirometric pulmonary function testing in patients with psoriasis. Objective: The aim of this study was to compare the spirometric parameters in patients with psoriasis and controls. Methods: Ninety-six patients with psoriasis and 60 sex- and age-matched control subjects were included in this study. Spirometric pulmonary function testing, including percent forced vital capacity (FVC%), percent forced expira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 19 publications
0
19
0
11
Order By: Relevance
“…Moreover, patients with psoriasis display increased risk of infections, especially respiratory infections including pneumonia . However, only a small single‐centre study of pulmonary function in participants with psoriasis is available …”
Section: Demographic Clinical and Spirometric Characteristics Of Thementioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, patients with psoriasis display increased risk of infections, especially respiratory infections including pneumonia . However, only a small single‐centre study of pulmonary function in participants with psoriasis is available …”
Section: Demographic Clinical and Spirometric Characteristics Of Thementioning
confidence: 99%
“…Although epidemiological studies have found increased risk of COPD and asthma only a single report is available on pulmonary function in psoriasis . These investigators found a reduced FEV 1 /FVC ratio but unaltered FEV 1 in participants with psoriasis ( n = 69) attending a dermatology clinic compared with controls with various other skin diseases .…”
Section: Demographic Clinical and Spirometric Characteristics Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…However, the connection fails to have been well-analysed. Both diseases are provoked by similar factors such as smoking, abdominal obesity, lack of physical activity, and concomitance of the metabolic syndrome [1][2][3].…”
Section: Introductionmentioning
confidence: 99%